Grossman & Baim's handbook of cardiac catheterization, angiography, and intervention - Moscucci, Mauro; Feldman, Marc D., 1958- (Philadelphia : Wolters Kluwer, 2014)
" An easily accessible, ready reference for the entire cardiac team, Grossman & Baim's Handbook of Cardiac Catheterization, Angiography, and Intervention is an essential resource in today's cardiac catheterization lab. This practical handbook, edited by Dr. Mauro Moscucci with contributions from associate editor, Marc D. Feldman, follows the bestselling text, Grossman & Baim's Cardiac Catheterization, Angiography, and Intervention, providing fast, convenient access to authoritative information in a portable handbook format. Covers all aspects of cardiac catheterization and intervention in an easy-to-manage, convenient handbook format Provides essential, quick-reference information for the entire cardiac team, including cardiovascular technologists, nurses, physicians, and fellows in training Includes sections on general principles (including radiation safety, complications, adjunctive pharmacotherapy, legal considerations, and issues specifically related to cardiovascular technologists and nursing care); basic techniques, hemodynamic principles, and angiographic techniques; the evaluation of cardiac function; special catheter techniques; coronary, peripheral, pediatric and structural heart disease interventions Enrich Your eBook Reading Experience Read directly on your preferred device(s), such as computer, tablet, or smartphone. Easily convert to audiobook, powering your content with natural language text-to-speech. "--
Companion volume to Grossman & Baim's cardiac catheterization, angiography, and intervention. Ninth edition. 2021.
Includes bibliographical references and index.
Keywords: Cardiac Catheterization -- methods; Cardiac Catheters; Coronary Angiography -- methods; Heart Diseases -- diagnosis; Heart Diseases -- therapy; MEDICAL / Cardiology; MEDICAL / Family & General Practice